Overcoming Barriers to Flare Reduction in Iran: A Techno-Economic and Policy Analysis of Modular NGL Solutions (Development Engineering Conferences Center Articles Database, 2025)
Gas flaring remains a major challenge in Iran, representing significant economic loss and environmental damage. While technical solutions exist, their implementation has been slow. This study presents an integrated analysis to address this gap, combining a techno-economic evaluation of a modular Mini-NGL unit at the Cheshmeh-Khosh oilfield with a legal and policy analysis of the barriers to its adoption. An Aspen HYSYS simulation confirmed the project's technical viability, and a discounted cash-flow analysis revealed exceptional profitability, with an IRR of 43.28% and a payback period of 1.8 years. However, our analysis of Iran's regulatory framework, benchmarked against international models (e.g., Nigeria, Russia, Norway) and its obligations under the UNFCCC and Paris Agreement [11], reveals that the primary obstacles are not technical or financial, but legal and institutional. The absence of binding domestic legislation and enforceable penalties hinders private investment despite high potential returns. The findings demonstrate that unlocking Iran's flared gas potential requires a paradigm shift from long-term policy goals to the enactment of a robust, predictable legal framework. This paper provides a roadmap for aligning Iran's economic interests with its international environmental commitments through scalable, profitable flare reduction projects.